Battling tuberculosis in an island context with a high burden of communicable and non-communicable diseases: epidemiology, progress, and lessons learned in Kiribati, 2000 to 2012. (January 2015) - Hoy, Damian; Kienene, Takeieta; Reiher, Bereka; Roth, Adam; Tira, Teatoa; McKenzie, Jeanie; Merilles, Onofre Edwin A.; Viney, Kerri
Highlights: We examined the epidemiology of tuberculosis (TB) in Kiribati from 2000 to 2012. Case notifications, incidence, and prevalence have increased since 2000. The 2015 goals for TB control are unlikely to be met. Kiribati has a complex mix of TB risk factors (e.g., smoking, diabetes, and alcohol). Summary: Objectives: To examine the epidemiology of tuberculosis (TB) in Kiribati from 2000 to 2012, document lessons learned, and recommend ways to mitigate the burden of TB in Kiribati. Methods: A descriptive study was performed using data on TB case notifications, prevalence, incidence, mortality, and treatment outcomes from global reports and data files. Progress towards meeting the Millennium Development Goal TB target (to reduce TB incidence by 2015) and the Regional Strategy to Stop Tuberculosis in the Western Pacific 2011–2015 targets (to reduce TB prevalence and mortality by half by 2015 relative to the level in 2000) was examined. Results: TB case notifications and the estimated incidence and prevalence have increased in Kiribati since 2000. From 2000 to 2012, Kiribati reported a total of 3863 TB notifications; in 2012, the case notification rate was 343/100 000 population. The majority (89%) of TB patients complete treatment and/or are cured, and the estimated TB mortality rate has remained relatively stable at around 16/100 000 population. HIV testing of TB patients has increased over recent years from 8% of notifications tested in 2003 to 43% tested in 2012. Of all 818 tests, only four (0.5%) patients were confirmed HIV-positive. Drug-resistant TB has been detected in a small number of cases. Conclusions: TB rates continue to increase in Kiribati and the 2015 goals for TB control are unlikely to be met. This is probably due to the complex mix of risk factors present in Kiribati, including smoking, diabetes, alcohol use, crowded living, and poverty. A comprehensive approach to address these risk factors is needed to mitigate the burden of TB in Kiribati.